A study on the relationship between High Performance Work System (HPWS) and the Employees performance in the Automotive Retail (After Sales) in Malaysia - Rani, Rashida Mat ,; Rahman, Normy Rafida Abdul; Yusak, Nurul Aqilah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This paper seeks to explore the relationship between HPWS and employee performance among service employees in Automotive Retail Companies in Malaysia. A review of literature will be used to posit how HPWS will influence employees’ performance. Previous studies principally show that organisation practicing HPWS is likely to give advantage to the organisation and employees performance. It is expected to enhance the HR practices effectiveness of the organisation in achieving the business target. The objectives of this study are to investigate the relationship between perceived-HPWS and service employee performance (task performance and service quality). Secondly, the relationship between perceived HPWS and service employees’ performance is mediated by perceived organisation support and psychological empowerment. This study focuses about HPWS and its components as well as employees’ perceptions of HPWS implementation within the organisation. Potential contributions succeeding this study are also discussed.